ANALISIS KELAYAKAN DAN STRATEGI PENGEMBANGAN USAHA TERNAK RUMINANSIA DI KABUPATEN SUMBAWA PASCA VIRUS PENYAKIT MULUT DAN KUKU - Rahim, Abdul; Sumarno, Teguh Adi (Jurnal Ekonomi & Bisnis, 2025)
This study aims to analyze businesses feasibility and formulate appropriate strategies in developing ruminant livestock businesses after the foot and mouth virus disease (FMD) in Sumbawa District. The type of this study was descriptive study. The type of data used in this study was quantitative data obtained directly from primary sources using research instruments in the form of interview guidelines. The sample selected to be used as research informants was 30 people who were determined using the simple random sampling technique. Data analysis in this study was carried out in two stages, firstly an R/C Ratio analysis to determine business feasibility, and secondly a SWOT analysis to formulate an appropriate strategy in developing ruminant livestock businesses in Sumbawa District. The results of this study showed that the R/C ratio value for ruminant livestock businesses in Sumbawa District was 1.559, which was greater than one (1.559>1), so that ruminant livestock businesses in Sumbawa District are profitable and worth continuing. The ruminant livestock business in Sumbawa District provides significant income for livestock farmers, so an appropriate development strategy is needed to increase the productivity of ruminant livestock farming in a sustainable manner. As for the results of the SWOT analysis produced four alternative strategies that can be implemented in developing ruminant livestock businesses in Sumbawa District, namely the SO strategy, WO strategy, ST strategy, and WT strategy.